2012
DOI: 10.1111/cas.12019
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptor coactivator RAC3 inhibits autophagy

Abstract: RAC3 is an oncogene naturally overexpressed in several tumors. Besides its role as coactivator, it can exert several protumoral cytoplasmic actions. Autophagy was found to act either as a tumor suppressor during the early stages of tumor development, or as a protector of the tumor cell in later stages under hypoxic conditions. We found that RAC3 overexpression inhibits autophagy when induced by starvation or rapamycin and involves RAC3 nuclear translocation-dependent and -independent mechanisms. Moreover, hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 27 publications
4
30
0
Order By: Relevance
“…In addition to our previous findings concerning the inhibitory role of RAC3 over apoptosis 5 , 35 and autophagy, 36 some recent works have demonstrated that RAC3 expression is necessary to maintain the pluripotency and self-renewal of stem cells. 37 , 38 , 39 The loss or downregulation of RAC3 is associated with differentiation of the stem cell to a mature cell type, 37 where the telomerase activity is expected to be silenced.…”
supporting
confidence: 52%
See 4 more Smart Citations
“…In addition to our previous findings concerning the inhibitory role of RAC3 over apoptosis 5 , 35 and autophagy, 36 some recent works have demonstrated that RAC3 expression is necessary to maintain the pluripotency and self-renewal of stem cells. 37 , 38 , 39 The loss or downregulation of RAC3 is associated with differentiation of the stem cell to a mature cell type, 37 where the telomerase activity is expected to be silenced.…”
supporting
confidence: 52%
“… 46 In addition, RAC3 overexpression is an autophagy inhibitor. 36 Figure 2c shows that both H 2 O 2 and rapamycin induced the increase of acid vesicles, compatible with autophagosomes, but RAC3 overexpression shows a clear inhibitory effect. Therefore, inhibition of autophagy could be one mechanism through which RAC3 overexpression inhibits the premature senescence.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations